2016
DOI: 10.1016/j.jstrokecerebrovasdis.2015.11.005
|View full text |Cite
|
Sign up to set email alerts
|

Association between Liver Disease and Intracranial Hemorrhage

Abstract: Background Liver disease is common and associated with clinical and laboratory evidence of coagulopathy. The association between liver disease and intracranial hemorrhage remains unclear. Our aim was to assess whether liver disease increases the risk of intracranial hemorrhage. Methods We performed a retrospective cohort study based on administrative claims data from California, Florida and New York acute care hospitals from 2005 through 2011. Of a random 5% sample, we included patients discharged from the e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
27
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 29 publications
(28 citation statements)
references
References 27 publications
1
27
0
Order By: Relevance
“…In our study, the inpatient mortality rate was higher in patients with liver disease. Similar findings were noted by Parikh et al 13 were liver disease was associated with an increased risk of ICH (HR: 1.8). Not unexpectedly, the mortality rate is higher in patients with underlying coagulopathy with use of oral anticoagulants a not uncommon association.…”
Section: Discussionsupporting
confidence: 89%
“…In our study, the inpatient mortality rate was higher in patients with liver disease. Similar findings were noted by Parikh et al 13 were liver disease was associated with an increased risk of ICH (HR: 1.8). Not unexpectedly, the mortality rate is higher in patients with underlying coagulopathy with use of oral anticoagulants a not uncommon association.…”
Section: Discussionsupporting
confidence: 89%
“…1 A similar relationship with ischemic stroke has not been observed. 2 However, liver disease, particularly cirrhotic liver disease, is complicated by an imbalanced coagulopathy with implications for both hemorrhagic and thrombotic processes.…”
mentioning
confidence: 82%
“…Kuo et al evaluated liver disease patients with CHA 2 DS 2 ‐VASc score ≥2 in the setting of AF and showed a reduction in ischemic stroke events in patients treated with warfarin compared with those with and without antiplatelet therapy, notably without increased intracranial hemorrhage 16. However, an increased risk of hemorrhagic stroke and intracranial hemorrhage has been reported in patients with cirrhosis as compared with those without,17, 18 and in 1 study was reported to be higher than ischemic stroke risk 19. A tailored strategy has been proposed and includes anticoagulation in the setting of less‐severe liver disease, while refraining from anticoagulation in more severe cirrhotic patients with AF 20.…”
Section: Discussionmentioning
confidence: 99%